The Influence of Social Media Use, Demographic, and Critical Thinking Skills on the Digital Citizenship - Titin Umi Lestari; Wibowo Heru Prasetiyo (Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the influence of social media use, demographic factors, and critical thinking skills on digital citizenship among students at the Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta. This study used a quantitative approach with a correlational design, involving 367 active student respondents who were selected proportionally from various study programs. The results indicate that social media use and critical thinking skills have a positive and significant effect on the digital citizenship. In addition, demographic factors such as gender, parental education, and level of study also have a significant relationship with digital citizenship. Mediation analysis shows that critical thinking skills can mediate the influence of social media use on digital citizenship, but do not mediate the influence of demographics. This study provides a new contribution by revealing the important role of critical thinking skills as a mediator between social media use and digital citizenship among prospective teacher students. These findings are useful for the development of digital literacy curricula in higher education, especially in strengthening digital citizenship competencies through the use of social media and the strengthening of critical thinking skills.